Digital Concrete: A Review. (September 2019) - Wangler, Timothy; Roussel, Nicolas; Bos, Freek P.; Salet, Theo A.M.; Flatt, Robert J.
Abstract: Digital fabrication techniques with concrete and cementitious materials have seen a large amount of research and industrial activity recently, with industrialization of techniques such as 3D printing becoming more of a reality. The potential to revolutionize construction is real, not only through reducing costs, but also bringing more sustainability and increased functionality. Material challenges are significant, chief among them understanding and controlling early age hydration and the link to rheology, incorporation of reinforcement, and overall, the link between processing, material, and performance, both from a structural and durability point of view. Interdisciplinarity is crucial, as the field brings together many disparate fields and has been driven by fields such as architecture so far. This article is a review of the state of the art in the newly forming field of digital fabrication with concrete, and aims to provide some direction in terms of the research challenges encountered thus far.